The BRAC : non-formal primary education programme in Bangladesh - Lovell, C. H.; Fatema, K. (New York : UNICEF, 1989)
The Bangladesh Rural Advancement Committee (BRAC) is the largest nongovernmental organization in Bangladesh. In 1985, in response to requests for rural poor people, it initiated a primary education program with experimental schools in 22 villages. By late 1989, the program had expanded to 2500 schools and another 2000 schools are expected to open in 1991. The objective of the program at its inception was to develop a replicable primary education model which could provide, in a 3-year period, basic literacy and numeracy to the poorest rural children who as yet had remained unreached by the formal school system. Experience with the program has proven that paraprofessional teachers, carefully but quickly trained and paid a small stipend, can be effective and that extensive parent and community involvement is important fore success. The program has shown that young village women and men can become dedicated and responsible teachers if they are well-selected and receive good basic training and continuing refresher courses, effective and consistent supervision, and structured guidance on what and how children should learn.
Includes bibliographical references
Keywords: Consumer Participation; Curriculum; Education; Organization and Administration; Program Evaluation; Rural Population; Demography; Developing Countries; Population; Population Characteristics; Asia; Bangladesh; Southern Asia; Evaluation Studies; Technical Report